(untitled) - Norris, Robert F. (Upper Saddle River, N.J., 2003)
This book presents readers with the basic principles of integrated pest management as they apply to plant pathogens, weeds, nematodes, mollusks, arthropods, and vertebrates. It reinforces the wisdom and soundness of the Integrated Pest Management (IPM) approach to crop protection, which attempts to limit the detrimental effects of pests in ways that are environmentally, economically, and socially acceptable. Includes diagrams and photographs as well as case histories and practical examples. Looks at the historical development of pest management, as well as IPM in the future. For pest management consultants and advisors, environmental issues specialists, gardeners, and public affairs activists.
Thâm cứu bảo vệ thực vật II
Keywords: Pests,Vật gây bệnh; Integrated control,Kiểm soát tích hợp